Pengaruh Lingkungan Belajar terhadap Minat Belajar Matematika Siswa Kelas VIII SMP Negeri 15 Yogyakarta - Indriana Puspita Dewi; Ibrahim Ibrahim (Departement of Mathematics Education, 2024)
The learning environment and learning interests are interconnected with each other. This study aims to examine the influence of the learning environment on the interest in learning mathematics of eighth grade students in SMPN 15 Yogyakarta. The method used is quantitative with the population in this study was 331 eighth grade learners with 67 respondents selected at random sampling. Primary data for this study were collected by distributing questionnaires to eighth grade students in SMPN 15 Yogyakarta. The software used is SPSS 25. The results of this study reveal that: First, Family Environment did not affect Learning Interest with a standard value at the P-value level > 0.05 (0.085 > 0.05); Second, School Environment did not affect Learning Interest with a standard value at the P-value level > 0.05 (0.146 > 0.05); Third, Community Environment has a significant effect on Learning Interest with a standard value at the P-value level<0.05 (0.000<0.05); Fourth, Family Environment, School Environment and Community Environment together have a significant effect on Learning Interest with an F-count of 19.301 > F-table of 2.7505 and the value of the coefficient of determination (R2) in R-Square obtains a value of 47.9%. Keywords: Learning Environment, Learning Interest